Population biology, conservation threats and status of Mediterranean striped dolphins (Stenella coeruleoalba) - Aguilar, Alex (J. Cetacean Res. Manage., 2000)
The paper reviews the information available on those aspects of the biology, ecology and effects of human impact that are relevant to the management and conservation of striped dolphins in the Mediterranean Sea. The striped dolphin is common throughout the western Mediterranean, although it shows a preference for open waters beyond the continental shelf. In 1991, the western Mediterranean population was estimated as 117,880 (95% CI = 68,379-214,800), but no comparable estimates are available for the eastern basin. Geographical variation in body length, skull morphometrics and genetic analyses, as well as the geographic range and evolution of the 1990-1992 epizootic, suggest some degree of isolation between dolphins in different regions within the Mediterranean and independence from those in the Atlantic. Growth and reproductive parameters in the Mediterranean are, overall, similar to those of other populations, with the exception of age at sexual maturity, which in both sexes is extremely high (11-12 years). Tissue levels of organochlorine compounds, some heavy metals and selenium are high and exceed threshold levels above which detrimental effects commonly appear in mammals. However, apart from the indication that these levels may have acted as triggering factors in the 1990-1992 epizootic by depressing the immune system of diseased individuals and potential lesions in the ovaries, no information on pollutant-related effects is available. The 1990-1992 epizootic devastated the whole Mediterranean population; over one thousand corpses were examined in the western Mediterranean alone, but the toll was probably much higher. The causative agent of the die-off was a morbillivirus, but the effect of some pollutants and decreased food availability were suggested as triggering factors. Depletion of fish and cephalopod resources is widespread in the Mediterranean and, given that the diet of striped dolphins includes commercial species, this undoubtedly has a potential for limiting population numbers. A number of fishing activities produce an associated striped dolphin bycatch. In particular, the pelagic driftnet fishery for tuna and swordfish, carried out by boats from Italy, Spain and Morocco, produces a significant kill in various locations. Variation in sighting and stranding frequency suggests that striped dolphins may have increased their numbers in recent decades. However, this progressive increase may have run parallel to a reduction in carrying capacity of its habitat. This suggestion is supported by the late age at attainment of sexual maturity observed in the Mediterranean population as compared to other conspecific or even congeneric populations.